Dilema Penerapan Pajak Karbon di Indonesia: Antara Komitmen Lingkungan dan Ketahanan Ekonomi Industri - Farsya Arafy Herlucky, Jasmine; Angta Laudia, Leivasya (DINASTI RESEARCH, 2024)
This research examines the dilemma of implementing carbon tax in Indonesia, specifically in balancing environmental commitments with industrial economic resilience. Using a mixed-method approach with sequential explanatory design, the study surveyed 511 respondents in the Greater Jakarta area. Results indicate that 81.41% of respondents rated the policy implementation effectiveness as moderate, while 82.2% considered implementation transparency to be at a moderate level. Regarding economic impact, 75.5% of respondents reported that the policy had a moderate intrusive level on the economy. These findings suggest a need to improve policy implementation mechanisms, particularly in monitoring aspects and information transparency. The study recommends a comprehensive strategy encompassing the development of industry incentive systems, periodic evaluations for more adaptive policy adjustments, and enhanced transparency and public engagement. In conclusion, a balanced approach is necessary to ensure carbon tax policies can achieve environmental objectives without causing excessive economic impact on the industrial sector and society.